2014
DOI: 10.1016/j.ymgme.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

A zebrafish model of hyperammonemia

Abstract: Hyperammonemia is the principal consequence of urea cycle defects and liver failure, and the exposure of the brain to elevated ammonia concentrations leads to a wide range of neurocognitive deficits, intellectual disabilities, coma and death. Current treatments focus almost exclusively on either reducing ammonia levels through the activation of alternative pathways for ammonia disposal or on liver transplantation. Ammonia is toxic to most fish and its pathophysiology appears to be similar to that in mammals. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 92 publications
0
8
0
Order By: Relevance
“…Hyperammonaemia leads to elevated extracellular glutamate concentrations, which hyperstimulates NMDAR ( Kosenko et al, 2003 ). Several NMDAR antagonists prevent hyperammonaemia-induced death in zebrafish ( Feldman et al, 2014 ). As reported previously, we observed that ammonium acetate (NH 4 Ac) treatment significantly decreased survival compared with the control sodium acetate (NaAc) treatment ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hyperammonaemia leads to elevated extracellular glutamate concentrations, which hyperstimulates NMDAR ( Kosenko et al, 2003 ). Several NMDAR antagonists prevent hyperammonaemia-induced death in zebrafish ( Feldman et al, 2014 ). As reported previously, we observed that ammonium acetate (NH 4 Ac) treatment significantly decreased survival compared with the control sodium acetate (NaAc) treatment ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since zebrafish larvae lack a functional urea cycle after hatching, they endogenously mimic the metabolic situation of patients with UCDs who suffer from the functional consequences of defective ureagenesis. Moreover, increasing the concentration of NH 4 + ions in the water by addition of NH 4 Ac is a convenient way to induce acute hyperammonemia in zebrafish larvae [ 38 ]. This approach enabled us to investigate the effects of toxic ammonium concentrations on biochemical and gene regulation as well as survival in a per se urea cycle-deficient organism including the efficacy of different therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…This effect could be attributed to the glycine based degradation products found in the material extracts of all the hydrogel samples. Nitrogen containing PBAE hydrogel and its degradation products are metabolized in the zebrafish liver into ammonia, a nitrogen waste product, which can cause local damage to the zebrafish . Since sample H3 has the least amount of glycine residues, it did not show liver damage, even at the highest concentration of extracts (200 µg mL −1 ).…”
Section: Resultsmentioning
confidence: 96%